Rancang Bangun Aplikasi Sistem Komunikasi Pengelolaan Reservasi antara Tenant Relation dan SPV Teknisi di Apartemen Margonda Residence 3, 4, dan 5 Depok Berbasis Web - Rayan Aditiya Permana; NM Faizah; Widyat Nurcahyo; Panser Karo-Karo (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2026)
Margonda Residence Apartments 3, 4, and 5 in Depok face challenges in managing unit maintenance reservations, primarily due to the absence of an integrated communication system between the Tenant Relation staff and the Technician Supervisor (SPV Teknisi). The manual process that has been in place leads to delayed responses, unclear work status, and difficulties in monitoring technician schedules in real time. This study aims to design and develop a web-based application to support a more structured reservation management process among Tenant Relation staff, Technician Supervisors, and apartment residents. The system was developed using the waterfall method, covering the stages of requirements analysis, system design, implementation, and testing. The resulting system includes features for reservation management, repair logs, technician management, inventory management, and an inter-user messaging system. This application is expected to accelerate the coordination of unit repairs and improve the operational efficiency of apartment management.